Volume 1: Additive Manufacturing; Advanced Materials Manufacturing; Biomanufacturing; Life Cycle Engineering; Manufacturing Equ 2020
DOI: 10.1115/msec2020-8473
|View full text |Cite
|
Sign up to set email alerts
|

Toward Structural Fatigue Analysis of Horizontally-Fabricated NiTi via Selective Laser Melting

Abstract: NiTi (Nitinol) is a shape memory alloy with distinctive properties, such as shape memory, superelasticity, biocompatibility, and low density. All these unique properties make NiTi a great candidate in different applications. However, the conventional fabrication of NiTi encounters many challenges that significantly limits the practical applications of the alloy. As a solution, the Selective Laser Melting (SLM) which is an Additive Manufacturing (AM) technique has been recently used for the fabrication of NiTi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The presence of such defects in NiTi tensile samples results in premature failure, lower fatigue life, and higher irrecoverable strain. 106,107 The type, size, and location of defects play a key role in the performance of LPBF-processed NiTi alloys. We have shown that, in parts with a vertical build direction, failure occurs sooner in comparison with samples fabricated horizontally.…”
Section: Thermomechanical Behavior Of Lpbf Niti Alloymentioning
confidence: 99%
“…The presence of such defects in NiTi tensile samples results in premature failure, lower fatigue life, and higher irrecoverable strain. 106,107 The type, size, and location of defects play a key role in the performance of LPBF-processed NiTi alloys. We have shown that, in parts with a vertical build direction, failure occurs sooner in comparison with samples fabricated horizontally.…”
Section: Thermomechanical Behavior Of Lpbf Niti Alloymentioning
confidence: 99%